They Will Never Forget How You Made Them Feel: Implementing Harm Reduction in the Perinatal Setting. - Puccio, Joelle (Maternal & Child Health Journal)
Harm reduction is a framework built upon respect for people who use drugs. Pregnancy is a priceless window of opportunity for positive change, when parents are driven to improve their health and well-being for their future child, and harm reduction can provide direction for this motivation. Perinatal harm reduction can include goals of abstinence, decreased use, safer use, or a goal unrelated to substance use, such as obtaining housing or employment. We engage in harm reduction, not only by promoting beneficial practices, but by eliminating harmful ones. Despite the science, effective program models, and overwhelming agreement that substance use disorder is a health condition and not deviant behavior, harm reduction programs for pregnant and parenting people are rare, and punitive treatment is the norm. To achieve equitable treatment for people with perinatal substance use disorder and protect the parent-infant dyad, we must stop harmful practices, respect the autonomy of people who use drugs, and address substance use disorders while increasing access to the social determinants of health.